Rigidez de solitons gradiente - Batista, Rondinelle Marcolino (2013)
Our goal in this work is to present a theorem which characterizes the gradient solitons rigid for non-compact case. As an application we prove that the homogeneous gradient solitons are rigid and provide an example of the Ricci soliton can not be gradient.